2019
DOI: 10.1007/s00268-019-05005-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Transcystic Versus Transductal Common Bile Duct Exploration: A Systematic Review and Meta‐analysis

Abstract: Objective To evaluate comparative outcomes of laparoscopic transcystic (TC) and transductal (TD) common bile duct (CBD) exploration. Methods We systematically searched MEDLINE, EMBASE, CINAHL, CENTRAL, the World Health Organization International Clinical Trials Registry, ClinicalTrials.gov, ISRCTN Register, and bibliographic reference lists. CBD clearance rate, perioperative complications, and biliary complications were defined as the primary outcome parameters. Procedure time, length of hospital stay, convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…The referencing order of the studies included in Table 2 starts from the most recently published papers. 19-54 Grading of the reviewed evidence was based on the content of Table 3. Statistical difference significance was considered to be P ≤ .05.…”
Section: Methodsmentioning
confidence: 99%
“…The referencing order of the studies included in Table 2 starts from the most recently published papers. 19-54 Grading of the reviewed evidence was based on the content of Table 3. Statistical difference significance was considered to be P ≤ .05.…”
Section: Methodsmentioning
confidence: 99%
“…These studies confirmed that LCBDE+LC using a transductal approach is safe and feasible for the management of CBD stones after gastrectomy. However, conventional LCBDE (ie, a transductal approach using a T‐tube, choledochoscopy, or primary closure) is associated with various complications, including bile duct stricture, bile leakage, prolonged biliary fistula, bleeding, and possible peritonitis after T‐tube removal 9,10 …”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic review and meta‐analysis of 2938 patients, the overall perioperative complication rate of LCBDE+LC by the transductal approach was 13.7%, and the biliary complication rate was 7.0% 9 . In addition, history of gastrectomy represents a risk factor for severe intra‐abdominal adhesions around the hepatoduodenal ligament.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the benefits of TC over TD LCBDE [6,7,25,26]. Although CBD clearance rates are similar between TC and TD approaches, TC LCBDE has lower overall complications, biliary complications, bloods loss and reduced length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%